2010
DOI: 10.1017/s0001924000003626
|View full text |Cite
|
Sign up to set email alerts
|

Starting characteristics of a rectangular supersonic air-intake with cowl deflection

Abstract: CR contraction ratio (A t /A c ) h cIntake capture height L overall length of model m e mass flow rate at diffuser exit (kg/s) m i capture mass flow rate (kg/s) P static pressure P b back pressure P bs sustainable back pressure P i free stream pressure P 0e total pressure at exit P 0i total pressure of free stream PE pressure ratio at exit (P b /P i ) θ 1 first ramp angle θ 2 second ramp angle θ 3 first diffuser angle θ 4 second diffuser angle θ c cowl deflection angle x distance from leading edge Y distance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…In order to bring out the condition at which the intake unstarting occurs, steady state simulations were also carried out for Mach 8,7,6,5,4,3.5,3.3,3.2 and 3 conditions respectively by varying the total pressure at inlet. Initially, all the simulations were carried out under adiabatic wall condition.…”
Section: Simulation For Different Free Stream Inlet Mach Number-unstamentioning
confidence: 99%
See 1 more Smart Citation
“…In order to bring out the condition at which the intake unstarting occurs, steady state simulations were also carried out for Mach 8,7,6,5,4,3.5,3.3,3.2 and 3 conditions respectively by varying the total pressure at inlet. Initially, all the simulations were carried out under adiabatic wall condition.…”
Section: Simulation For Different Free Stream Inlet Mach Number-unstamentioning
confidence: 99%
“…Das and Prasad 6 have conducted both experimental and numerical investigation of mixed compression intake flow field at Mach 2.2 with different cowl deflections and showed that small angle at the cowl lip leads to start of the intake and improve its performance. Experimental and numerical studies of Dirk, et al 7 demonstrate that bleed can reduce boundary layer separation and improve the inlet total pressure recovery.…”
Section: Introductionmentioning
confidence: 99%
“…7 and 8, we also consider an expanded computational domain in order to take into account a shock wave arising ahead of the lower wall. The configuration (1)-(3) will produce a flow pattern similar to a region downstream of oblique shocks generated by the compression wedge of a typical intake [3]. Its examination will contribute to the understanding of flow instability mechanisms in sophisticated intakes used in practice.…”
Section: Formulation Of the Problem For 2d Flowmentioning
confidence: 99%
“…They concluded that a definite increase in performance and flow quality by cowl bending and adopting bleed. Staring characteristics for intake with cowl deflection were also studied by Das and Prasad [2], concluded that cowl defection could be thought of an alternative to the bleeding for the intake model. Two dimensional simulations corresponding to different cowl bending studied by same authors [3] concluded that the increase in cowl deflection angle increased the performance for the intake model with pressurized exit and small deflection led to good pressure recovery.…”
Section: State Of the Art Technologymentioning
confidence: 99%